Burundi : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
Burundi is in great need of investment in infrastructure, but fiscal constraints leave little room for additional public spending. Despite this initial recovery, Burundi has yet to rebuild its pre-civil war level of public capital stock. Improving the business climate is one of the keys to attracting higher private investment. Since the Arusha agreement, some progress in the business climate has been made. Burundi is quickly moving away from the unsustainable debt situation and unstable exchange rate of the 1990s.